A review on the applications of image logs in structural analysis and sedimentary characterization. (August 2018) - Lai, Jin; Wang, Guiwen; Wang, Song; Cao, Juntao; Li, Mei; Pang, Xiaojiao; Han, Chuang; Fan, Xuqiang; Yang, Liu; He, Zhibo; Qin, Ziqiang
Abstract: Image logs provide important information on lithology, sedimentary textures, paleoflow directions, fractures and in situ stress analysis. Lacking of criteria used for establishing the image log facies limits the applications of image logs in sedimentary reservoir interpretation. This paper provides a thoroughgoing review focusing on the recent applications of borehole image logs for sedimentological and structural description and interpretation, and aims to establish image log facies which can provide guidelines in sedimentary reservoir interpretation. This paper firstly summarizes the principles and basic characteristics of various imaging logging tools, and then briefly introduces the pre-processing workflow of the image log data. Then the generated images are used for depth and orientation shifts of cores by calibrating individual sedimentary and structural features. Descriptive and concise image log facies are established based on combinations of image textures including dip type, dip pattern, and color scheme, and the characteristics as well as physical criteria for each individual image facies are summarized. The established image log facies are then interpreted in terms of structural and sedimentological features such as lithology, sedimentary structures, vugs, fractures and faults. The image log facies and its stacking patterns are then used to interpret the lithofacies associations by calibrating with cores and conventional logs. Natural fractures and induced fractures are recognized by image logs, and the principles of breakouts and drilling-induced fractures for in-situ stress analysis are reviewed. Then the applications of image logs in investigation of fracture attitudes and states, as well as in computation of fracture parameters are summarized. The procedures to evaluate fracture effectiveness through image logs are discussed. At last, the application of image logs for structural dip analysis is reviewed, and image logs are used for recognizing faults, fracture sets, and attitudes of stratum through the dip patterns. The basic procedures for paleocurrent reconstruction, which includes dip picking of cross beddings, structural dip determination and structural dip removal, are reviewed. Then the paleocurrent directions of the Lower Cretaceous Bashijiqike Formation in the Kuqa depression were reconstructed, which could help further understanding of the depositional systems. This review will help extend the utility of image logs in interpreting small to large -scale sedimentary and structural features, and bridges the gaps between well log analysis and sedimentary and structural interpretation. Highlights: The principles and basic characteristics of imaging logging tools were summarized. Descriptive and concise image log facies are established. The procedures to evaluate fracture effectiveness through image logs are discussed. Image logs are used for structural dip analysis and paleocurrent reconstruction.